PENERAPAN TEKNIK COACHING MODEL TIRTA DALAM SUPERVISI AKADEMIK UNTUK MENINGKATKAN KUALITAS PEMBELAJARAN DI SDN 1 GUNEM - Safikin; Siti Khanifah; Wahyuni Rahma Dianti; Ngurah Ayu Nyoman Murniati; Siti Ari Mursalina (STKIP Subang, 2024)
Examining the use of the TIRTA coaching model technique in academic supervision and its impact on raising the standard of instruction at SDN 1 Gunem is the goal of this study. The first issue brought up is how using the TIRTA coaching model may impact the standard of academic supervision-based learning. Bandura's social cognitive theory, which highlights the value of reinforcement in social interactions to promote constructive changes in the learning process, is the theory applied in this study. Understanding the dynamics and significance of the academic supervision process employed in schools is the goal of the descriptive qualitative research method with a phenomenological perspective. According to the study's findings, the principal regularly uses the TIRTA coaching model in academic supervision with the intention of supporting teachers in their joint learning process rather than evaluating their skills. By using this paradigm, teachers can communicate their learning difficulties in a more relaxed and open environment, which improves collaboration between the principal and teachers. Additionally, using the TIRTA coaching approach helps teachers become more creative and inovative educators who can execute varied instruction based on the requirements and learning styles of their students. The quality of learning in the classroom will benefit from this since it will be more efficient and responsive.